Simultaneous extraction of cadmium, nickel, and cobalt ions from acidic aqueous solutions by emulsion liquid membrane using sunflower-kerosene mixture as a diluent; breakage and mass transfer studies - Hayder K. Admawi; Ahmed A. Mohammed (Results in Surfaces and Interfaces, 2024)
In this study, a simultaneous removal of cadmium, cobalt, and nickel from an aqueous solution through the Green Emulsion Liquid Membrane (GELM) method was carried out. A 7:3 ratio of sunflower oil to kerosene was utilized as the membrane phase stabilized by Span 80 as the emulsifier. D2EHPA as a carrier and HCl as an inner phase were used. Extraction and stripping efficiencies of 97.45% and 98.42% for Cd2+, 96.82% and 97.84% for Co2+, 89.74% and 92.69% for Ni2+, respectively, with the lowest breakage (0.8%) were obtained under the best operating conditions. An extensive investigation of the influence of homogenizer speed, external and internal phase acidity, the HLB value of the surfactant (Tween 80 and Span 80), surfactant and carrier concentrations, volume ratio of the membrane to internal phase, mixer speed, ratio of external to membrane phase emulsification time and extraction time on the stability of membrane, extraction, and stripping efficiencies were carried out. Kinetic analysis of cadmium, cobalt, and nickel extraction was performed using zero, first, and second-order models at optimum conditions. The experimental data fit well with first-order for three metal ions. The coefficient of the total mass transfer (Ft) of cadmium through the GELM technique was 3.28% higher than that of cobalt and 28.61% higher than that of nickel, while the Ft of cobalt is 25.33% higher than that of nickel. Using the recovered membrane, the extraction of the three metal ions for the initial six cycles was extremely efficient under the best conditions.